TEACHER TALK AND STUDENTS TALK IN EFL CLASS ACTIVITY: SECONDARY SCHOOL CONTEXT - Pricilia Tupalessy; Marcy S. Ferdinandus; Hellien Jequelin Loppies (Wiralodra English Journal, 2024)
The study focuses on the dynamics and types of teacher and student talks in EFL classrooms. It highlights whether teacher or student talk dominates class and impacts students' language acquisition. It was conducted in an Eastern Indonesian secondary school and employed exploratory sequential mixed methods. The data were collected from an English teacher and 32 students through interviews and observations. Thematic analysis and relative frequency distribution table were used for data analysis. The findings showed that teacher talk dominated classroom activities and made student-centred learning lacking, thus affecting students' language acquisition. Various teacher and student talk categories were identified using the Flander Interaction Analysis Category (FIAC) framework. Teacher Talk (TT) involved indirect influences such as accepting feelings, praises or encourages, using students' ideas, and asking questions. The direct influence includes lecture, giving directions, and criticizing students' behaviour. While Student Talk (ST) had students' responses, students-initiated silence and confusion. Implications suggest enhancing teachers' conversation management skills and fostering a more student-centred approach to facilitate students' language practice and participation. Additionally, future researchers who wish to conduct similar research can develop deeper by looking at other aspects that positively impact interaction in the English language classroom.